Nodular lesions on the upper trunk: An uncommon anatomical site of renal tumor metastases - Nikolaos Kostopoulos; Eftychia Platsidaki; Vasiliki Tzanetakou; Konstantina Petraki; Maria Lekarakou; Dimitrios Bafaloukos; Irini Potouridou (Wolters Kluwer Medknow Publications, 2019)
Renal cell carcinoma (RCC) is the most frequent cancer of the kidney and it accounts for 3% of all solid malignancies. Although rare, cutaneous metastases can be an important manifestation of RCC. We present a case of a 56-year-old male with a history of RCC, followed by the development of cutaneous metastases 4 years later with an uncommon clinical presentation. RCC is the most common genitourinary cancer to metastasize to the skin and accounts for 6.8% of cutaneous metastases. These patients have a poor prognosis. It is essential for these patients to perform a complete periodic dermatologic examination for proper restaging and treatment.